Semantic analysis of object phrases verbal component in the light of O. Potebnya’s conception - Анютіна, Ганна Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article focuses on the influence of O. Potebnya’s conception on the development oc modern linguistics. The problem of language and thinking interrelation in O. Potebnya’s works is considered. The article analyses object phrases verbal component in the light of O. Potebnya’s conception. Object relations as relations arising when the process of thinking combines two separate notions in one complex concept are analyzed. The semantics of the verbal element as a factor defining the semantic subclass of the noun functioning as an object syntactic element is characterized. Some semantic groups of the verb showing discrimination in the relation to the object are considered. The problem of object phrases and the compound verbal predicate differentiation is analyzed on the base of scientific technical texts. The types of the compound verbal predicate representing verbal noun phrases are described and analyzed. The selective character of the verbal noun phrases and their specific functioning are stated.